155k views
3 votes
Let f ( x ) = 3 x + 5 and g ( x ) = 3 x 2 + 3 x . After simplifying, ( f ∘ g ) ( x ) =

Let f ( x ) = 3 x + 5 and g ( x ) = 3 x 2 + 3 x . After simplifying, ( f ∘ g ) ( x-example-1

1 Answer

3 votes

Answer

Step-by-step explanation

Given:


f(x)=3x+5
g(x)=3x^2+3x

To determine (f º g)(x), we plug in the value of g(x) into f(x) as shown below:


\begin{gathered} (f\circ g)(x)=f(g(x)) \\ =f(3x^2+3x) \\ =3(3x^2+3x)+5 \\ Simplify \\ (f\circ g)(x)=9x^2+9x+5 \end{gathered}

Therefore, the answer is:


(f\circ g)(x)=9x^(2)+9x+5

User Wmk
by
6.5k points